2019
DOI: 10.1080/19336918.2019.1639303
|View full text |Cite
|
Sign up to set email alerts
|

TIMP-2 inhibits metastasis and predicts prognosis of colorectal cancer via regulating MMP-9

Abstract: Colorectal cancer has a common cause of morbidity and mortality. Therefore, it is urgent to detect reliable biomarkers to predict prognosis in CRC. Here, we determined the expression of TIMP-2 and MMP-9 in a  CRC tissue microarray by immunohistochemistry. We found that lower TIMP-2 or/and higher MMP-9 expression in cancer tissues was correlated with poorer overall survival (OS). TIMP-2 or MMP-9 expression was independent prognostic factors for CRC. Furthermore, TIMP-2 and MMP-9 expression had a synergistic rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 39 publications
1
36
1
Order By: Relevance
“…Correspondingly, in case of HSF and OR inhibition to (active) MMP‐2 secretion, with no LPS responsiveness, might possibly be associated with an increase of TIMP‐2 levels as well. The last publication reported that decreased levels of TIMP‐2 were closely related to poor prognosis of CRC metastasis (Wang et al., 2019),…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, in case of HSF and OR inhibition to (active) MMP‐2 secretion, with no LPS responsiveness, might possibly be associated with an increase of TIMP‐2 levels as well. The last publication reported that decreased levels of TIMP‐2 were closely related to poor prognosis of CRC metastasis (Wang et al., 2019),…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, TIMP-2, tissue inhibitor of metalloproteinases (TIMPs) family, has also been identified in our study. TIMP-2 was described to decrease cell proliferation and migration in vitro via the inhibition of MMPs ( 46 ). However, it is associated with poor patient outcomes in cancers including gastric ( 47 ), renal ( 48 ), and oral squamous cell cancers ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF has a role in granulopoiesis and anti-inflammation. 29 TIMP-2 30,31 and TGF-b are mildly elevated. 32 TIMP2 actively attenuates the negative remodelling and TGFb2 is involved in tissue repair.…”
Section: Elevated Cytokinesmentioning
confidence: 97%